GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Genetic and ecological evidence for cryptic divergence within a species complex of rockfish in the Eastern Pacific - Anita Wray; R. N. Lou; G. Longo; W. Larson; P. H. Sudmant; J. Benante; J. H. Harms; J. R. Hyde; K. M. Nichols (Conservation Genetics, 2026)

The MIREN Road Survey Database: Standardized Vegetation Sampling to Advance Our Understanding of Biodiversity Responses in Mountain Systems Across the Globe - Sylvia Haider; Jonas J. Lembrechts; Jake Alexander; Vincent Ralph Clark; Lisa J. Rew; Meike Buhaly; Marc Achermann; Alla Aleksanyan; Alisa Alvarez; Marco Andrello; José R. Arévalo; Valeria Aschero; et al. (Global Ecology and Biogeography, 2026)
Motivation The database initiated by the Mountain Invasion Research Network (MIREN) is one of the few globally implemented standardized vegetation surveys in mountains. The focus is on collecting plant species occurrences at 5‐year intervals along and adjacent to mountain roads spanning elevational gradients, with the goal of providing critical information about the ongoing spread of non‐native plants and the potential impacts of climate and human‐caused disturbance in the form of road infrastructure on mountain vegetation. Main Types of Variables Contained To date, the database contains almost 170,000 georeferenced records of plant species. Overall, 6854 vascular plant species were observed in 3364 plots across 25 regions, with many of these plots being revisited every 5 years. Each plot is identified by its coordinates, elevation and distance to the road. The status of each individual species (native, non‐native or unknown) is determined in accordance with regional databases. Spatial Location and Grain Plant species were surveyed at 20 sample sites, placed at regular elevational intervals along each mountain road, with typically three roads selected per region. Each sample site is subdivided into three 2 m × 50 m plots, one parallel to the road and two perpendicular to it, extending into adjacent vegetation. The 25 studied regions cover all continents except Antarctica. Time Period and Grain Data were collected between 2007 and 2023, with surveys being repeated at 5‐year intervals in a subset of regions. Three regions include four time‐steps, while seven and three regions were sampled three times or twice, respectively. In most regions, long‐term monitoring is ongoing. Major Taxa and Level of Measurement All vascular plant species. Software Format Data are available through a .csv file on Zenodo ( https://doi.org/10.5281/zenodo.15749536 ).

Neuroimmune Correlates of HIV and Marijuana Use: Peripheral Biomarkers and Cognitive Function - Michaela E. Larson; E. Alfonso Romero-Sandoval; Sheri L. Towe; Adam W. Carrico; Christina S. Meade (Journal of Neuroimmune Pharmacology, 2026)

Immunoblot-based activity assay for heme-containing histidine kinases - Grant W. Larson; Eaindra Yee; Ambika Bhagi-Damodaran; Anoop Rama Damodaran (JBIC Journal of Biological Inorganic Chemistry, 2026)

Relationships among peri-traumatic circulating endocannabinoids and long-term, negative outcomes following traumatic injury - Emily A. Albertina; Carissa W. Tomas; Timothy J. Geier; Sydney C. Timmer-Murillo; Isela G. Pina; Kelley Jazinski-Chambers; Garrett Sauber; Jacklynn M. Fitzgerald; Christine L. Larson; Terri A. deRoon-Cassini; Cecilia J. Hillard (Psychopharmacology, 2026)
Rationale Traumatically injured individuals can develop chronic negative psychological sequelae. Improved understanding of contributing, peri-traumatic risk factors is essential to reduce the risk of these consequences. Previous studies have found that peri-traumatic, circulating endocannabinoid concentrations are positively associated with development of post-traumatic stress disorder (PTSD), chronic pain and depression months later, particularly in members of racial/ethnic groups that have been historically marginalized. Objectives This replication study examined relationships among peri-trauma serum endocannabinoid concentrations and long-term consequences in a cohort comprised primarily of individuals from marginalized racial and ethnic groups. Methods Participants ( n = 100; 81% from marginalized racial and ethnic groups) were traumatically injured adults presenting to the ED of an urban tertiary care hospital. Endocannabinoids N -arachidonoylethanolamine (AEA) and 2-arachidonoylglycerol (2-AG) were measured in serum collected within days (peri-trauma) and 6–10 months following injury (follow-up). Assessments, including PTSD, depression, pain and quality of life were completed. Statistical approaches, including multivariate, hierarchical regressions, were used to determine associations among serum endocannabinoid concentrations and long-term outcomes. Results Although it did not survive correction for multiple comparisons, peri-trauma serum 2-AG concentrations. Peri-trauma serum 2-AG concentrations were also positively associated with PTSD, pain severity, and functional engagement scores at follow-up. There were no significant associations between circulating 2-AG or AEA and depression. Conclusions These findings generally replicate earlier studies demonstrating that serum 2-AG concentrations are biomarkers of risk for PTSD and pain and uncover an additional association with poor functional quality of life. Further studies are needed to determine the underlying mechanisms of these relationships.

Pyrethroid insecticide pollution of wetlands reduces amphipod density - Breanna R. Keith; Danelle M. Larson; Carl W. Isaacson; Michael J. Anteau; Megan J. Fitzpatrick; Jake D. Carleen (Ecotoxicology, 2025)

Stimulant Use, HIV, and Plasma Metabolites Among Men - Emily M. Cherenack; Michaela E. Larson; Kevin Murray; Zachary J. Mayer; Candace Guerrero; Courtney A. Broedlow; Nichole R. Klatt; Adam W. Carrico (Journal of Neuroimmune Pharmacology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Quaternary intensification of spine epibiosis in the cidaroid echinoid Eucidaris: implications for anthropogenic impacts - Elizabeth Petsios; Corinne E. Fuchs; Michal Kowalewski; Paul Larson; Roger W. Portell; Carrie L. Tyler (Frontiers in Marine Science, 2025)
Echinoids are an integral part of present-day and ancient marine trophic webs, and they host a variety of mutualistic, commensalistic, and parasitic epibionts on their spines and test. Cidaroid echinoid (slate pencil urchins) spines in particular are commonly colonized by epizoans. Eucidaris in the western Atlantic and eastern Pacific today are notable for the frequency and intensity of calcifying, non-calcifying, and galling colonization on their spines. While moderate levels of spine colonization may provide camouflage and other benefits to the host, a high density of encrusters may instead reduce host fitness, and galling is invariably parasitic. Significant environmental changes in the equatorial and sub-equatorial western Atlantic and eastern Pacific necessitate a paleobiological approach to constrain the timing of changes in epibiosis intensity on Eucidaris . Here, we compare rates of spine colonization in present-day Eucidaris populations with ancestral Pliocene Eucidaris assemblages. We find that Pliocene spines show no evidence of parasitic galling, and significantly less evidence of epibiosis than their present-day descendants in both the Atlantic and Pacific. This holds true even after accounting for taphonomic processes that would preferentially erase evidence of non-calcifying colonization. We propose that the high intensity of colonization on present-day Eucidaris spines is a relatively recent development and may reflect human-induced habitat degradation in the region, underscoring the need for further investigation into this biotic interaction.

Linking functional responses and effects with stoichiometric traits - Eric K. Moody; Katie Anania; Kate S. Boersma; Tyler J. Butts; Jessica R. Corman; Spencer Cruz; W. Reilly Farrell; Kauan N. Fonseca; Amy C. Krist; Erin I. Larson; Alex Lewanski; Christian Liriano; et al. (Ecology, 2025)
Trait‐based approaches to study biodiversity responses to changing environmental conditions have become popular because these approaches provide context to how and why certain taxa shift in abundance within an assemblage. Trait‐based approaches also offer the potential to link shifts in assemblage composition to effects on ecosystem functions like rates of primary production, detrital decomposition, and nutrient uptake. However, focusing on response traits in multidimensional functional diversity studies limits our ability to make these linkages. We developed a multidimensional analytical and visual stoichiometric diversity framework that links organismal responses to and effects on environmental change using stoichiometric traits. We define these traits as the acquisition, assimilation, allocation, and excretion of key chemical elements by members of an assemblage. We discuss the considerations for using stoichiometric traits in a trait‐based framework and apply the framework to case studies of temporal variation in stream benthic invertebrate assemblages and spatial variation in urban woody vegetation assemblages. These examples illustrate the utility of the stoichiometric diversity framework for testing stoichiometric hypotheses and suggest promising linkages between assemblage shifts and shifts in ecosystem function.

Fish Invasion of Prairie Pothole Wetlands Reduces Amphipod Abundance, A Key Vertebrate Forage - Jake D. Carleen; Danelle M. Larson; Michael J. Anteau; Megan J. Fitzpatrick; Andrew W. Hafs; Carl W. Isaacson; Breanna R. Keith (Wetlands, 2024)

Setting an Environmental Baseline for the Deep-Sea Slope Offshore Northwestern Cuba (Southeastern Gulf of Mexico) Using Sediments and Nematode Diversity - Maickel Armenteros; Diana Marzo-Pérez; José Andrés Pérez-García; Patrick T. Schwing; Alexei Ruiz-Abierno; Misael Díaz-Asencio; Rebekka A. Larson; Gregg R. Brooks; David W. Hastings; Adolfo Gracia; Steven A. Murawski (Thalassas: An International Journal of Marine Sciences, 2024)
Deep-sea offshore northwestern Cuba is the less studied zone of the Gulf of Mexico (GoM). Our study aimed to set an environmental baseline and investigate a potential west-east gradient of sediment properties and nematode diversity along the northwestern Cuba. Sediments were collected by multicorer at nine sites in the insular slope between 974 and 1682 m depth. Sediment texture and composition showed a west-east gradient caused likely by narrowing of shelf width and increasing of downslope transport of terrigenous material. We found clear signatures of heavy metal pollution likely derived from Havana City but also from open-sky mining (Castellanos mining complex) and port dredging operations (Mariel). Nematode assemblages were dominated by the deep-sea genera: Acantholaimus, Metadasynemella, Desmodorella, Cervonema, Daptonema, Halalaimus , and Pselionema . α-diversity was about 20–50 genera and γ-diversity of about 100 genera. The β-diversity was substantial likely because small-scale patchiness of resources and heavy metals stress that increased assemblage variability. Individual weight decreased with depth indicating food-supply limitation in the deep sea; also, heavy metals were negatively correlated with weight suggesting deleterious effects on the growing. Our findings indicate that heavy metal pollution has reached deep-sea sediments and corroborate the long-range effects of anthropogenic activities on deep sea. Taxonomic diversity and biological traits (life strategy and trophic composition) constituted a powerful bioindicator of benthic health and benchmark for future potential disturbances in the region. Northwestern Cuba slope is still an understudied portion of the GoM and more research is needed to fully understand its biodiversity and biogeochemical patterns.

Niche conservatism and spread explain introgression between native and invasive fish - Jordan H. Hartman; Joel Corush; Eric R. Larson; Jeremy S. Tiemann; Philip W. Willink; Mark A. Davis (Molecular Ecology, 2024)
Hybridisation can be an important driver of evolutionary change, but hybridisation with invasive species can have adverse effects on native biodiversity. While hybridisation has been documented across taxa, there is limited understanding of ecological factors promoting patterns of hybridisation and the spatial distribution of hybrid individuals. We combined the results of ecological niche modelling (ENM) and restriction site‐associated DNA sequencing to test theories of niche conservatism and biotic resistance on the success of invasion, admixture, and extent of introgression between native and non‐native fishes. We related Maxent predictions of habitat suitability based on the native ranges of invasive Eastern Banded Killifish ( Fundulus diaphanus diaphanus Lesueur 1817) and native Western Banded Killifish ( Fundulus diaphanus menona Jordan and Copeland 1877) to admixture indices of individual Banded Killifish. We found that Eastern Banded Killifish predominated at sites predicted as suitable from their ENM, consistent with niche conservatism. Admixed individuals were more common as Eastern Banded Killifish habitat suitability declined. We also found that Eastern Banded Killifish were most common at sites closest to the presumed source of this invasion, whereas the proportion of admixed individuals increased with distance from the source of invasion. Lastly, we found little evidence that habitat suitability for Western Banded Killifish provides biotic resistance from either displacement by, or admixture with, invasive Eastern Banded Killifish. Our study demonstrates that ENMs can inform conservation‐relevant outcomes between native and invasive taxa while emphasising the importance of protecting isolated Western Banded Killifish populations from invasive conspecifics.

Wilder rangelands as a natural climate opportunity: Linking climate action to biodiversity conservation and social transformation - Lavhelesani D. Simba; Mariska te Beest; Heidi-Jayne Hawkins; Keith W. Larson; Anthony R. Palmer; Camilla Sandström; Kathleen G. Smart; Graham I. H. Kerley; Joris P. G. M. Cromsigt (Ambio, 2024)
Rangelands face threats from climate and land-use change, including inappropriate climate change mitigation initiatives such as tree planting in grassy ecosystems. The marginalization and impoverishment of rangeland communities and their indigenous knowledge systems, and the loss of biodiversity and ecosystem services, are additional major challenges. To address these issues, we propose the wilder rangelands integrated framework, co-developed by South African and European scientists from diverse disciplines, as an opportunity to address the climate, livelihood, and biodiversity challenges in the world’s rangelands. More specifically, we present a Theory of Change to guide the design, monitoring, and evaluation of wilder rangelands. Through this, we aim to promote rangeland restoration, where local communities collaborate with regional and international actors to co-create new rangeland use models that simultaneously mitigate the impacts of climate change, restore biodiversity, and improve both ecosystem functioning and livelihoods.

Cardiovascular and mood responses to an acute bout of cold water immersion - Emma L. Reed; Christopher L. Chapman; Emma K. Whittman; Talia E. Park; Emily A. Larson; Brendan W. Kaiser; Lindan N. Comrada; Karen Wiedenfeld Needham; John R. Halliwill; Christopher T. Minson (Journal of Thermal Biology, 2023)

A cosmogenic 10Be moraine chronology of arid, alpine Late Pleistocene glaciation in the Pioneer Mountains of Montana, USA - Spruce W. Schoenemann; Mana M. Bryant; Will B. Larson; Lee B. Corbett; Paul R. Bierman (Quaternary Science Reviews, 2023)

Sound Level Changes the Auditory Cortical Activation Detected with Functional Near-Infrared Spectroscopy - Sterling W. Sheffield; Eric Larson; Iliza M. Butera; Andrea DeFreese; Baxter P. Rogers; Mark T. Wallace; G. Christopher Stecker; Adrian K. C. Lee; Rene H. Gifford (Brain Topography, 2023)

The phylogeny and global biogeography of Primulaceae based on high-throughput DNA sequence data - Drew A. Larson; Andre S. Chanderbali; Olivier Maurin; Deise J.P. Gonçalves; Christopher W. Dick; Douglas E. Soltis; Pamela S. Soltis; Peter W. Fritsch; James J. Clarkson; Aurélie Grall; Nina M.J. Davies; Isabel Larridon; et al. (Molecular Phylogenetics and Evolution, 2023)

Good Practices for the Laboratory Performance Testing of Aqueous Oral Inhaled Products (OIPs): an Assessment from the International Pharmaceutical Aerosol Consortium on Regulation and Science (IPAC-RS) - Jolyon P. Mitchell; I. Carter; J. D. Christopher; M. Copley; W. H. Doub; A. Goodey; C. J. Gruenloh; B. B. Larson; S. Lyapustina; R. B. Patel; S. W. Stein; J. D. Suman (AAPS PharmSciTech, 2023)

Resource allocation and rising complexity during the Iron Age IIA: An isotopic case study from Khirbet Summeily, Israel - Kara Larson; Elizabeth Arnold; James W. Hardin (Quaternary International, 2023)

Learning from arid and urban aquatic ecosystems to inform more sustainable and resilient futures - Lauren McPhillips; Marta Berbés-Blázquez; Rebecca Hale; Tamara K. Harms; Vanya Bisht; Liliana Caughman; Sandra M. Clinton; Elizabeth Cook; Xiaoli Dong; Jennifer Edmonds; Sarah Gergel; Rosa Gómez; et al. (Journal of Hydrology, 2023)

Corrigendum: Associations between cyanobacteria and indices of secondary production in the western basin of Lake Erie - James H. Larson; Mary Anne Evans; Robert J. Kennedy; Sean W. Bailey; Keith A. Loftin; Zachary R. Laughrey; Robin A. Femmer; Jeff S. Schaeffer; William B. Richardson; Timothy T. Wynne; J. C. Nelson; Joseph W. Duris (Limnology and Oceanography, 2022)
In the last year, we became aware that data used in our above‐referenced manuscript from 2018 published in Limnology and Oceanography contained significant errors. In the 2018 manuscript, we found that indices of secondary production were negatively correlated to indices of cyanobacterial abundance and toxicity. Unfortunately, one of our indices of cyanobacterial abundance (biovolume) and our measurement of toxicity (microcystin concentration) were inaccurate in the data we used in the 2018 manuscript. Upon discovering these errors, we immediately began correcting the repositories where these data were available. Having corrected those data repositories, we are now reporting on the re‐analysis of the data using the methods previously described in the 2018 manuscript. Although the relationships are slightly different, our interpretation is that the conclusions of the 2018 manuscript are still valid using the corrected data. The data errors we experienced were traced to a spreadsheet that was used to share data among the research team, which had errors caused by mistakes in copy‐pasting formulas instead of data and ‘inadvertent’ edits that were saved by the spreadsheet's auto‐save function. We apologize to the scientific community for these errors.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

A unifying framework for analyzing temporal changes in functional and taxonomic diversity along disturbance gradients - Erin I. Larson; N. LeRoy Poff; W. Chris Funk; Rachel A. Harrington; Boris C. Kondratieff; Scott G. Morton; Alexander S. Flecker (Ecology, 2021)
Frameworks exclusively considering functional diversity are gaining popularity, as they complement and extend the information provided by taxonomic diversity metrics, particularly in response to disturbance. Taxonomic diversity should be included in functional diversity frameworks to uncover the functional mechanisms causing species loss following disturbance events. We present and test a predictive framework that considers temporal functional and taxonomic diversity responses along disturbance gradients. Our proposed framework allows us to test different multidimensional metrics of taxonomic diversity that can be directly compared to calculated multidimensional functional diversity metrics. It builds on existing functional diversity–disturbance frameworks both by using a gradient approach and by jointly considering taxonomic and functional diversity. We used previously unpublished stream insect community data collected prior to, and for the two years following, an extreme flood event that occurred in 2013. Using 14 northern Colorado mountain streams, we tested our framework and determined that taxonomic diversity metrics calculated using multidimensional methods resulted in concordance between taxonomic and functional diversity responses. By considering functional and taxonomic diversity together and using a gradient approach, we were able to identify some of the mechanisms driving species losses following this extreme disturbance event.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Ancient DNA suggests modern wolves trace their origin to a Late Pleistocene expansion from Beringia - Liisa Loog; Olaf Thalmann; Mikkel‐Holger S. Sinding; Verena J. Schuenemann; Angela Perri; Mietje Germonpré; Herve Bocherens; Kelsey E. Witt; Jose A. Samaniego Castruita; Marcela S. Velasco; Inge K. C. Lundstrøm; Nathan Wales; et al. (Molecular Ecology, 2020)
Grey wolves ( Canis lupus ) are one of the few large terrestrial carnivores that have maintained a wide geographical distribution across the Northern Hemisphere throughout the Pleistocene and Holocene. Recent genetic studies have suggested that, despite this continuous presence, major demographic changes occurred in wolf populations between the Late Pleistocene and early Holocene, and that extant wolves trace their ancestry to a single Late Pleistocene population. Both the geographical origin of this ancestral population and how it became widespread remain unknown. Here, we used a spatially and temporally explicit modelling framework to analyse a data set of 90 modern and 45 ancient mitochondrial wolf genomes from across the Northern Hemisphere, spanning the last 50,000 years. Our results suggest that contemporary wolf populations trace their ancestry to an expansion from Beringia at the end of the Last Glacial Maximum, and that this process was most likely driven by Late Pleistocene ecological fluctuations that occurred across the Northern Hemisphere. This study provides direct ancient genetic evidence that long‐range migration has played an important role in the population history of a large carnivore, and provides insight into how wolves survived the wave of megafaunal extinctions at the end of the last glaciation. Moreover, because Late Pleistocene grey wolves were the likely source from which all modern dogs trace their origins, the demographic history described in this study has fundamental implications for understanding the geographical origin of the dog.

Fixing a snag in carbon emissions estimates from wildfires - Jeffrey E. Stenzel; Kristina J. Bartowitz; Melannie D. Hartman; James A. Lutz; Crystal A. Kolden; Alistair M. S. Smith; Beverly E. Law; Mark E. Swanson; Andrew J. Larson; William J. Parton; Tara W. Hudiburg (Global Change Biology, 2019)
Wildfire is an essential earth‐system process, impacting ecosystem processes and the carbon cycle. Forest fires are becoming more frequent and severe, yet gaps exist in the modeling of fire on vegetation and carbon dynamics. Strategies for reducing carbon dioxide (CO 2 ) emissions from wildfires include increasing tree harvest, largely based on the public assumption that fires burn live forests to the ground, despite observations indicating that less than 5% of mature tree biomass is actually consumed. This misconception is also reflected though excessive combustion of live trees in models. Here, we show that regional emissions estimates using widely implemented combustion coefficients are 59%–83% higher than emissions based on field observations. Using unique field datasets from before and after wildfires and an improved ecosystem model, we provide strong evidence that these large overestimates can be reduced by using realistic biomass combustion factors and by accurately quantifying biomass in standing dead trees that decompose over decades to centuries after fire (“snags”). Most model development focuses on area burned; our results reveal that accurately representing combustion is also essential for quantifying fire impacts on ecosystems. Using our improvements, we find that western US forest fires have emitted 851 ± 228 Tg CO 2 (~half of alternative estimates) over the last 17 years, which is minor compared to 16,200 Tg CO 2 from fossil fuels across the region.

Preload Sensitivity with TORVAD Counterpulse Support Prevents Suction and Overpumping - Jeffrey R. Gohean; Erik R. Larson; Raul G. Longoria; Mark Kurusz; Richard W. Smalling (Cardiovascular Engineering and Technology, 2019)

Parallel signatures of selection at genomic islands of divergence and the major histocompatibility complex in ecotypes of sockeye salmon across Alaska - Wesley A. Larson; Tyler H. Dann; Morten T. Limborg; Garrett J. McKinney; James E. Seeb; Lisa W. Seeb (Molecular Ecology, 2019)
Understanding the genetic mechanisms that facilitate adaptive radiation is an important component of evolutionary biology. Here, we genotyped 82 neutral SNPs, seven SNPs in islands of divergence identified in a previous study (island SNPs), and a region of the major histocompatibility complex (MHC) in 32 populations of sockeye salmon to investigate whether conserved genes and genomic regions are involved in adaptive radiation. Populations representing three ecotypes were sampled from seven drainages with differing habitats and colonization histories spanning a range of 2,000 km. We found strong signatures of parallel selection across drainages at the island SNPs and MHC, suggesting that the same loci undergo divergent selection during adaptive radiation. However, patterns of differentiation at most island SNPs and the MHC were not associated with ecotypes, suggesting that these loci are responding differently to a mosaic of selective pressures. Our study provides some of the first evidence that conserved genomic islands may be involved in adaptive divergence of salmon populations. Additionally, our data provide further support for the hypothesis that sockeye salmon inhabiting rivers unconnected to lakes harbour similar genetic diversity across large distances, are likely the ancestral form of the species, and have repeatedly recolonized lake systems as they have become available after glacial recession. Finally, our results highlight the value and importance of validating outlier loci by screening additional populations and regions, a practice that will hopefully become more common in the future.

Identification of Bighead Carp and Silver Carp early-life environments and inferring Lock and Dam 19 passage in the Upper Mississippi River: insights from otolith chemistry - Gregory W. Whitledge; Brent Knights; Jon Vallazza; James Larson; Michael J. Weber; James T. Lamer; Quinton E. Phelps; Jacob D. Norman (Biological Invasions, 2019)

Future Directions in Sea Otter Research and Management - Randall W. Davis; James L. Bodkin; Heather A. Coletti; Daniel H. Monson; Shawn E. Larson; Lilian P. Carswell; Linda M. Nichol (Frontiers in Marine Science, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Novel RAD sequence data reveal a lack of genomic divergence between dietary ecotypes in a landlocked salmonid population - Morten T. Limborg; Wesley A. Larson; Kyle Shedd; Lisa W. Seeb; James E. Seeb (Conservation Genetics Resources, 2018)

Extreme streams: species persistence and genomic change in montane insect populations across a flooding gradient - N. LeRoy Poff; Erin I. Larson; Patricia E. Salerno; Scott G. Morton; Boris C. Kondratieff; Alexander S. Flecker; Kelly R. Zamudio; W. Chris Funk (Ecology Letters, 2018)
The ecological and evolutionary consequences of extreme events are poorly understood. Here, we tested predictions about species persistence and population genomic change in aquatic insects in 14 Colorado mountain streams across a hydrological disturbance gradient caused by a one in 500‐year rainfall event. Taxa persistence ranged from 39 to 77% across sites and declined with increasing disturbance in relation to species' resistance and resilience traits. For taxa with mobile larvae and terrestrial adult stages present at the time of the flood, average persistence was 84% compared to 25% for immobile taxa that lacked terrestrial adults. For two of six species analysed, genomic diversity (allelic richness) declined after the event. For one species it greatly expanded, suggesting resilience via re‐colonisation from upstream populations. Thus, while resistance and resilience traits can explain species persistence to extreme disturbance, population genomic change varies among species, challenging generalisations about evolutionary responses to extreme events at landscape scales.

Associations between cyanobacteria and indices of secondary production in the western basin of Lake Erie - James H. Larson; Mary Anne Evans; Robert J. Kennedy; Sean W. Bailey; Keith A. Loftin; Zachary R. Laughrey; Robin A. Femmer; Jeff S. Schaeffer; William B. Richardson; Timothy T. Wynne; J. C. Nelson; Joseph W. Duris (Limnology and Oceanography, 2018)
Large lakes provide a variety of ecological services to surrounding cities and communities. Many of these services are supported by ecological processes that are threatened by the increasing prevalence of cyanobacterial blooms which occur as aquatic ecosystems experience cultural eutrophication. Over the past 10 yr, Lake Erie experienced cyanobacterial blooms of increasing severity and frequency, which have resulted in impaired drinking water for the surrounding communities. Cyanobacterial blooms may impact ecological processes that support other services, but many of these impacts have not been documented. Secondary production (production of primary consumers) is an important process that supports economically important higher trophic levels. Cyanobacterial blooms may influence secondary production because cyanobacteria are a poor‐quality food resource and cyanotoxins may be harmful to consumers. Over 3 yr at 34 sites across the western basin of Lake Erie, we measured three indices of secondary production that focus on the dominant bivalve taxa: (1) growth of a native unionid mussel, (2) the size of young‐of‐year dreissenid mussels, and (3) the mass of colonizing animals on a Hester‐Dendy sampler. Associations between these indices and cyanobacterial data were estimated to assess whether cyanobacteria are associated with variation in secondary production in the western basin of Lake Erie. The results suggest cyanobacterial abundance alone is only weakly associated with secondary production, but that cyanotoxins have a larger effect on secondary production. Given recurring late‐summer cyanobacterial blooms, this impact on secondary production has the potential to undermine Lake Erie's ability to sustain important ecosystem services.

Alien plants as mediators of ecosystem services and disservices in urban systems: a global review - Luke J. Potgieter; Mirijam Gaertner; Christoph Kueffer; Brendon M. H. Larson; Stuart W. Livingstone; Patrick J. O’Farrell; David M. Richardson (Biological Invasions, 2017)

Screening of duplicated loci reveals hidden divergence patterns in a complex salmonid genome - Morten T. Limborg; Wesley A. Larson; Lisa W. Seeb; James E. Seeb (Molecular Ecology, 2017)
A whole‐genome duplication ( WGD ) doubles the entire genomic content of a species and is thought to have catalysed adaptive radiation in some polyploid‐origin lineages. However, little is known about general consequences of a WGD because gene duplicates (i.e., paralogs) are commonly filtered in genomic studies; such filtering may remove substantial portions of the genome in data sets from polyploid‐origin species. We demonstrate a new method that enables genome‐wide scans for signatures of selection at both nonduplicated and duplicated loci by taking locus‐specific copy number into account. We apply this method to RAD sequence data from different ecotypes of a polyploid‐origin salmonid ( Oncorhynchus nerka ) and reveal signatures of divergent selection that would have been missed if duplicated loci were filtered. We also find conserved signatures of elevated divergence at pairs of homeologous chromosomes with residual tetrasomic inheritance, suggesting that joint evolution of some nondiverged gene duplicates may affect the adaptive potential of these genes. These findings illustrate that including duplicated loci in genomic analyses enables novel insights into the evolutionary consequences of WGD s and local segmental gene duplications.

Tall fescue forage mass in a grass-legume mixture: predicted efficiency of indirect selection - Blair L. Waldron; Michael D. Peel; Steven R. Larson; Ivan W. Mott; J. Earl Creech (Euphytica, 2017)

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

Genomic islands of divergence linked to ecotypic variation in sockeye salmon - Wesley A. Larson; Morten T. Limborg; Garrett J. McKinney; Daniel E. Schindler; James E. Seeb; Lisa W. Seeb (Molecular Ecology, 2017)
Regions of the genome displaying elevated differentiation (genomic islands of divergence) are thought to play an important role in local adaptation, especially in populations experiencing high gene flow. However, the characteristics of these islands as well as the functional significance of genes located within them remain largely unknown. Here, we used data from thousands of SNP s aligned to a linkage map to investigate genomic islands of divergence in three ecotypes of sockeye salmon ( Oncorhynchus nerka ) from a single drainage in southwestern Alaska. We found ten islands displaying high differentiation among ecotypes. Conversely, neutral structure observed throughout the rest of the genome was low and not partitioned by ecotype. One island on linkage group So13 was particularly large and contained six SNP s with F ST > 0.14 (average F ST of neutral SNP s = 0.01). Functional annotation revealed that the peak of this island contained a nonsynonymous mutation in a gene involved in growth in other species ( TULP 4 ). The islands that we discovered were relatively small (80–402 Kb), loci found in islands did not show reduced levels of diversity, and loci in islands displayed slightly elevated linkage disequilibrium. These attributes suggest that the islands discovered here were likely generated by divergence hitchhiking; however, we cannot rule out the possibility that other mechanisms may have produced them. Our results suggest that islands of divergence serve an important role in local adaptation with gene flow and represent a significant advance towards understanding the genetic basis of ecotypic differentiation.

Erratum to: Spatial and temporal dynamics of ascidian invasions in the continental United States and Alaska - Christina Simkanin; Paul W. Fofonoff; Kristen Larson; Gretchen Lambert; Jennifer A. Dijkstra; Gregory M. Ruiz (Marine Biology, 2016)

Spatial and temporal dynamics of ascidian invasions in the continental United States and Alaska - Christina Simkanin; Paul W. Fofonoff; Kristen Larson; Gretchen Lambert; Jennifer A. Dijkstra; Gregory M. Ruiz (Marine Biology, 2016)

The application of genomics to inform conservation of a functionally important reef fish (Scarus niger) in the Philippines - Brian L. Stockwell; Wesley A. Larson; Ryan K. Waples; Rene A. Abesamis; Lisa W. Seeb; Kent E. Carpenter (Conservation Genetics, 2016)

Effects of age on arterial stiffness and central blood pressure after an acute bout of resistance exercise - Robert S. Thiebaud; Christopher A. Fahs; Lindy M. Rossow; Jeremy P. Loenneke; Daeyeol Kim; J. Grant Mouser; Travis W. Beck; Debra A. Bemben; Rebecca D. Larson; Michael G. Bemben (European Journal of Applied Physiology, 2016)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Signals of heterogeneous selection at an MHC locus in geographically proximate ecotypes of sockeye salmon - Wesley A. Larson; James E. Seeb; Tyler H. Dann; Daniel E. Schindler; Lisa W. Seeb (Molecular Ecology, 2014)
The genes of the major histocompatibility complex ( MHC ) are an important component of the vertebrate immune system and can provide insights into the role of pathogen‐mediated selection in wild populations. Here, we examined variation at the MHC class II peptide‐binding region in 27 populations of sockeye salmon ( Oncorhynchus nerka ), distributed among three distinct spawning ecotypes, from a complex of interconnected rivers and lakes in south‐western Alaska. We also obtained genotypes from 90 putatively neutral single nucleotide polymorphisms for each population to compare the relative roles of demography and selection in shaping the observed MHC variation. We found that MHC divergence was generally partitioned by spawning ecotype (lake beaches, rivers and streams) and was 30 times greater than variation at neutral markers. Additionally, we observed substantial differences in modes of selection and diversity among ecotypes, with beach populations displaying higher levels of directional selection and lower MHC diversity than the other two ecotypes. Finally, the level of MHC differentiation in our study system was comparable to that observed over much larger geographic ranges, suggesting that MHC variation does not necessarily increase with increasing spatial scale and may instead be driven by fine‐scale differences in pathogen communities or pathogen virulence. The low levels of neutral structure and spatial proximity of populations in our study system indicate that MHC differentiation can be maintained through strong selective pressure even when ample opportunities for gene flow exist.

Genetic control of rhizomes and genomic localization of a major-effect growth habit QTL in perennial wildrye - Lan Yun; Steve R. Larson; Ivan W. Mott; Kevin B. Jensen; Jack E. Staub (Molecular Genetics and Genomics, 2014)

Reproductive Success and Body Size in the Cricket Gryllus firmus - Nicholas W. Saleh; Erica L. Larson; Richard G. Harrison (Journal of Insect Behavior, 2014)

Development and application of genomic tools to the restoration of green abalone in southern California - K. M. Gruenthal; D. A. Witting; T. Ford; M. J. Neuman; J. P. Williams; D. J. Pondella; A. Bird; N. Caruso; J. R. Hyde; L. W. Seeb; W. A. Larson (Conservation Genetics, 2014)

Community‐specific impacts of exotic earthworm invasions on soil carbon dynamics in a sandy temperate forest - Jasmine M. Crumsey; James M. Le Moine; Yvan Capowiez; Mitchell M. Goodsitt; Sandra C Larson; George W. Kling; Knute J. Nadelhoffer (Ecology, 2013)
Exotic earthworm introductions can alter above‐ and belowground properties of temperate forests, but the net impacts on forest soil carbon (C) dynamics are poorly understood. We used a mesocosm experiment to examine the impacts of earthworm species belonging to three different ecological groups ( Lumbricus terrestris [anecic], Aporrectodea trapezoides [endogeic], and Eisenia fetida [epigeic]) on C distributions and storage in reconstructed soil profiles from a sandy temperate forest soil by measuring CO 2 and dissolved organic carbon (DOC) losses, litter C incorporation into soil, and soil C storage with monospecific and species combinations as treatments. Soil CO 2 loss was 30% greater from the Endogeic × Epigeic treatment than from controls (no earthworms) over the first 45 days; CO 2 losses from monospecific treatments did not differ from controls. DOC losses were three orders of magnitude lower than CO 2 losses, and were similar across earthworm community treatments. Communities with the anecic species accelerated litter C mass loss by 31–39% with differential mass loss of litter types ( Acer rubrum > Populus grandidentata > Fagus grandifolia > Quercus rubra ≥ Pinus strobus ) indicative of leaf litter preference. Burrow system volume, continuity, and size distribution differed across earthworm treatments but did not affect cumulative CO 2 or DOC losses. However, burrow system structure controlled vertical C redistribution by mediating the contributions of leaf litter to A‐horizon C and N pools, as indicated by strong correlations between (1) subsurface vertical burrows made by anecic species, and accelerated leaf litter mass losses (with the exception of P. strobus ); and (2) dense burrow networks in the A‐horizon and the C and N properties of these pools. Final soil C storage was slightly lower in earthworm treatments, indicating that increased leaf litter C inputs into soil were more than offset by losses as CO 2 and DOC across earthworm community treatments.

A new dromaeosaurid (Dinosauria: Theropoda) with Asian affinities from the latest Cretaceous of North America - David C. Evans; Derek W. Larson; Philip J. Currie (The Science of Nature, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Cocaine self-administration behaviors in ClockΔ19 mice - Angela Renee Ozburn; Erin Beth Larson; David W. Self; Colleen A. McClung (Psychopharmacology, 2012)

Climatic niche divergence or conservatism? Environmental niches and range limits in ecologically similar damselflies - Maren Wellenreuther; Keith W. Larson; Erik I. Svensson (Ecology, 2012)
The factors that determine species' range limits are of central interest to biologists. One particularly interesting group comprises odonates (dragonflies and damselflies), which show large differences in secondary sexual traits and respond quickly to climatic factors, but often have minor interspecific niche differences, challenging models of niche‐based species coexistence. We quantified the environmental niches at two geographic scales to understand the ecological causes of northern range limits and the coexistence of two congeneric damselflies ( Calopteryx splendens and C. virgo ). Using environmental niche modeling, we quantified niche divergence first across the whole geographic range in Fennoscandia, and second only in the sympatric part of this range. We found evidence for interspecific divergence along the environmental axes of temperature and precipitation across the northern range in Fennoscandia, suggesting that adaptation to colder and wetter climate might have allowed C. virgo to expand farther north than C. splendens . However, in the sympatric zone in southern Fennoscandia we found only negligible and nonsignificant niche differences. Minor niche differences in sympatry lead to frequent encounters and intense interspecific sexual interactions at the local scale of populations. Nevertheless, niche differences across Fennoscandia suggest that species differences in physiological tolerances limit range expansions northward, and that current and future climate could have large effects on the distributional ranges of these and ecologically similar insects.

Evaluation of the Diurnal Cycle in the Atmospheric Boundary Layer Over Land as Represented by a Variety of Single-Column Models: The Second GABLS Experiment - G. Svensson; A. A. M. Holtslag; V. Kumar; T. Mauritsen; G. J. Steeneveld; W. M. Angevine; E. Bazile; A. Beljaars; E. I. F. de Bruijn; A. Cheng; L. Conangla; J. Cuxart; et al. (Boundary-Layer Meteorology, 2011)

Rethinking the evolution of extant sub‐Saharan African suids (Suidae, Artiodactyla) - Jaime Gongora; Rebecca E. Cuddahee; Fabrícia Ferreira do Nascimento; Christopher J. Palgrave; Stewart Lowden; Simon Y. W. Ho; Denbigh Simond; Chandramaya Siska Damayanti; Daniel James White; Wee Tek Tay; Ettore Randi; Hans Klingel; et al. (Zoologica Scripta, 2011)
Gongora, J., Cuddahee, R. E., do Nascimento, F. F., Palgrave, C. J., Lowden, S., Ho, S. Y. W., Simond, D., Damayanti, C. S., White, D. J., Tay, W. T., Randi, E., Klingel, H., Rodrigues‐Zarate, C. J., Allen, K., Moran, C. & Larson, G. (2011). Rethinking the evolution of extant sub‐Saharan African suids (Suidae, Artiodactyla). — Zoologica Scripta, 40 , 327–335. Although African suids have been of scientific interest for over two centuries, their origin, evolution, phylogeography and phylogenetic relationships remain contentious. There has been a long‐running debate concerning the evolution of pigs and hogs (Suidae), particularly regarding the phylogenetic relationships among extant Eurasian and African species of the subfamily Suinae. To investigate these issues, we analysed the mitochondrial and nuclear DNA sequences of extant genera of Suidae from Eurasia and Africa. Molecular phylogenetic analyses revealed that all extant sub‐Saharan African genera form a monophyletic clade separate from Eurasian suid genera, contradicting previous attempts to resolve the Suidae phylogeny. Two major sub‐Saharan African clades were identified, with Hylochoerus and Phacochoerus grouping together as a sister clade to Potamochoerus. In addition, we find that the ancestors of extant African suids may have evolved separately from the ancestors of modern day Sus and Porcula in Eurasia before they colonised Africa. Our results provide a revision of the intergeneric relationships within the family Suidae.

Grid soil sampling adoption and abandonment in cotton production - Jonathan C. Walton; Roland K. Roberts; Dayton M. Lambert; James A. Larson; Burton C. English; Sherry L. Larkin; Steven W. Martin; Michele C. Marra; Kenneth W. Paxton; Jeanne M. Reeves (Precision Agriculture, 2010)

Assignment to breeding and wintering grounds using stable isotopes: a comment on lessons learned by Rocque et al. - Keith W. Larson; Keith A. Hobson (Journal of Ornithology, 2009)

Genes controlling plant growth habit in Leymus (Triticeae): maize barren stalk1 (ba1), rice lax panicle, and wheat tiller inhibition (tin3) genes as possible candidates - Parminder Kaur; Steven R. Larson; B. Shaun Bushman; Richard R.-C. Wang; Ivan W. Mott; David Hole; Jyothi Thimmapuram; George Gong; Lei Liu (Functional & Integrative Genomics, 2008)

Factors affecting farmer adoption of remotely sensed imagery for precision management in cotton production - James A. Larson; Roland K. Roberts; Burton C. English; Sherry L. Larkin; Michele C. Marra; Steven W. Martin; Kenneth W. Paxton; Jeanne M. Reeves (Precision Agriculture, 2008)

Interactions between auditory and somatosensory feedback for voice F 0 control - Charles R. Larson; Kenneth W. Altman; Hanjun Liu; Timothy C. Hain (Experimental Brain Research, 2008)

Character and significance of spectacular layering features developed in the thin, alkali-basaltic sills of the Ulvö Gabbro Complex, Sweden - S. Å. Larson; K. J. Hogmalm; W. P. Meurer (Mineralogy and Petrology, 2008)

Measurements of spectral optical properties and their relation to biogeochemical variables and processes in Crater Lake, Crater Lake National Park, OR - Emmanuel S. Boss; Robert Collier; Gary Larson; Katja Fennel; W. S. Pegau (Hydrobiologia, 2007)

Distribution and abundance of zooplankton populations in Crater Lake, Oregon - Gary L. Larson; C. David McIntire; Mark W. Buktenica; Scott F. Girdner; Robert E. Truitt (Hydrobiologia, 2007)

Predicting Secchi disk depth from average beam attenuation in a deep, ultra-clear lake - Gary L. Larson; Robert L. Hoffman; Bruce R. Hargreaves; Robert W. Collier (Hydrobiologia, 2007)

Ultraviolet radiation and bio-optics in Crater Lake, Oregon - B. R. Hargreaves; S. F. Girdner; M. W. Buktenica; R. W. Collier; E. Urbach; G. L. Larson (Hydrobiologia, 2007)

Variability of kokanee and rainbow trout food habits, distribution, and population dynamics, in an ultraoligotrophic lake with no manipulative management - Mark W. Buktenica; Scott F. Girdner; Gary L. Larson; C. David McIntire (Hydrobiologia, 2007)

Thermal, chemical, and optical properties of Crater Lake, Oregon - Gary L. Larson; Robert L. Hoffman; David C. McIntire; Mark W. Buktenica; Scott F. Girdner (Hydrobiologia, 2007)

Microtopographic control of vascular plant, bryophyte and lichen communities on cliff faces - Kathryn Lynne Kuntz; Douglas W. Larson (Plant Ecology, 2006)

Influences of Microhabitat Constraints and Rock‐Climbing Disturbance on Cliff‐Face Vegetation Communities - KATHRYN LYNNE KUNTZ; DOUGLAS W. LARSON (Conservation Biology, 2006)
Many researchers report that rock climbing has significant negative effects on cliff biota. Most work on climbing disturbance, however, has not controlled for variation in microsite characteristics when comparing areas with and without climbing presence. Additionally, some researchers do not identify the style or difficulty level of climbing routes sampled or select climbing routes that do not represent current trends in the sport. We solved these problems by sampling climbing areas used by advanced “sport” climbers and quantifying differences in microtopography between climbed and control cliffs. We determined whether differences in vegetation existed between pristine and sport‐climbed cliff faces when microsite factors were not controlled. We then determined the relative influence of the presence of climbing, cliff‐face microtopography, local physical factors, and regional geography on the richness, abundance, and community composition of cliff‐face vascular plants, bryophytes, and lichens. When we did not control for microsite differences among cliffs, our results were consistent with the majority of prior work on impacts of climbing (i.e., sport‐climbed cliff faces supported a lower mean richness of vascular plants and bryophytes and significantly different frequencies of individual species when compared with pristine cliff faces). When we investigated the relative influences of microtopography and climbing disturbance, however, the differences in vegetation were not related to climbing disturbance but rather to the selection by sport climbers of cliff faces with microsite characteristics that support less vegetation. Climbed sites had not diverged toward a separate vegetation community; instead, they supported a subset of the species found on pristine cliff faces. Prior management recommendations to restrict development of new climbing routes should be reevaluated based on our results.

Phylogeographic analysis of mitochondrial gene flow and introgression in the salamander, Plethodon shermani - D. W. WEISROCK; K. H. KOZAK; A. LARSON (Molecular Ecology, 2005)
Plethodon shermani comprises a series of geographically disjunct populations occupying high‐elevation mountain isolates. These populations hybridize at their borders with salamanders of the Plethodon glutinosus species complex, and past range expansions inferred from Pleistocene climatic cycles may have increased the possible genetic interactions between P. shermani and species of the P. glutinosus complex. Because mitochondrial DNA haplotypes often show introgression across species borders, we survey mtDNA variation for evidence of past and ongoing genetic interactions between P. shermani, its close relative Plethodon cheoah, and species of the P. glutinosus complex. Ongoing hybridization with the P. glutinosus ‐complex species Plethodon teyahalee is accompanied by extensive mitochondrial introgression in some Unicoi populations of P. shermani, but it has little genetic impact on P. shermani populations outside hybrid zones at three other isolates (Tusquitee, Wayah Bald, Standing Indian). Some Unicoi populations of P. shermani exhibit mtDNA evidence of past hybridization with diverse lineages from P. aureolus and P. glutinosus . The Tusquitee isolate of P. shermani is also characterized by mtDNA haplotypes most closely related to Plethodon aureolus and P. glutinosus , presumably introduced by past genetic contact with these species or with introgressed populations of Unicoi P. shermani . The mtDNA variation in sampled populations of the Wayah Bald and Standing Indian isolates of P. shermani appears largely unaffected by ongoing hybridization. Principal components analyses of allozymic data indicate that P. shermani isolates collectively form a genetically homogeneous unit clearly demarcated from species with which they have had current or past genetic interactions. Rapid mtDNA introgression associated with transient contacts between P. shermani and other species permits a fine‐level resolution of evolutionary lineages not evident from allozymic data.

Dominance As An Overlooked Measure of Invader Success - Jeremy T. Lundholm; Douglas W. Larson (Biological Invasions, 2004)

Experimental separation of resource quantity from temporal variability: seedling responses to water pulses - Jeremy T. Lundholm; Douglas W. Larson (Oecologia, 2004)

Effects of Rock Climbing on the Land Snail Community of the Niagara Escarpment in Southern Ontario, Canada - Michele A. McMillan; Jeffrey C. Nekola; Douglas W. Larson (Conservation Biology, 2003)
The cliffs of the Niagara Escarpment provide habitat for extremely diverse communities of land snails that may be at risk as a result of recreational rock climbing. We examined the effects of rock climbing on the density, richness, diversity, and community composition of snails on the Niagara Escarpment in southern Ontario, Canada. We sampled from randomly selected climbed and unclimbed sections of cliffs on the plateau ( cliff edge ), cliff face, and talus ( cliff base ). Snail density, richness, and diversity were lower along climbing routes than in unclimbed areas, and community composition differed between climbed and unclimbed samples. These results suggest that rock climbing has significant negative effects on all aspects of the snail community on cliffs; therefore, we recommend the inclusion of gastropods in conservation plans for protected areas containing cliffs.

Effects of Rock Climbing on the Vegetation of the Niagara Escarpment in Southern Ontario, Canada - Michele A. McMillan; Douglas W. Larson (Conservation Biology, 2002)
The cliffs of the Niagara Escarpment support unique and diverse plant communities. Although recreational rock climbing has become extremely popular in North America over the past two decades, little is known about the effect of this sport on the natural biota. We examined the ecological effects of rock climbing on vascular plant, bryophyte, and lichen communities along the Niagara Escarpment in southern Ontario. We made comparisons among randomly selected climbed and unclimbed rock outcrops by sampling from three positions: plateau (or cliff edge), cliff face, and talus (or cliff base). Density, percent cover, species richness, and species diversity of vascular plants were lower on climbed outcrops than on unclimbed outcrops. In addition, the proportion of alien plants was three times greater in climbed areas than in unclimbed areas. The frequency and richness of bryophyte species were also significantly lower in climbed areas. The frequency of lichens was the same on climbed and unclimbed cliffs, but species richness was significantly lower in climbed areas, and community composition differed between climbed and unclimbed areas. Our results suggest that rock climbing has significant negative effects on all aspects of the vegetative community on cliffs. Therefore, we recommend that conservation plans be modified to include specific policies regarding recreational rock climbing for lands containing exposed cliffs. For example, we suggest that the establishment of new climbing routes be banned in protected areas along the Niagara Escarpment.

Arsenic Concentrations in House Wrens from Whitewood Creek, South Dakota, USA - T. W. Custer; C. M. Custer; S. Larson; K. K. Dickerson (Bulletin of Environmental Contamination and Toxicology, 2002)

Community structure of epilithic lichens on the cliffs of the Niagara Escarpment, Ontario, Canada - Uta Matthes; Bruce D. Ryan; Douglas W. Larson (Plant Ecology, 2000)

Evidence for the widespread occurrence of ancient forests on cliffs - D. W. Larson; U. Matthes; J. A. Gerrath; N. W. K. Larson; J. M. Gerrath; J. C. Nekola; G. L. Walker; S. Porembski; A. Charlton (Journal of Biogeography, 2000)
Aim The objective of this work was to determine if the existence of ancient forests on cliffs was specific to the Niagara Escarpment, Canada, or part of a globally widespread pattern. Location Sixty‐five cliff sites were visited in five countries in the temperate climatic zone, and trees were sampled for age and growth rate on forty‐six of these. Methods Two hundred and twenty‐four core samples or cross‐sections were taken from trees on cliffs that varied in height, aspect, rock‐type, and exposure. General observations were also made of regeneration of the tree species forming the mature canopy, and other habitat conditions. Results The evidence shows that ancient slow‐growing forest occurs on most cliffs. Age and growth rate distributions were similar at all treed sites. Small‐statured Thuja, Juniperus , or Taxus stems with age estimates in excess of 1000 years were found in the United States, the United Kingdom and France, and small Pinus and Quercus stems nearly 400 years in Germany. There was a high rate of recurrence of plants in the genera Polypodium , Asplenium , Cystopteris , Campanula , Rosa , Prunus , Hedera , and Sorbus . Most of the sites appear to be habitats of completely natural origin. Conclusions We conclude that ancient natural forest is a normal feature of cliffs, at least in the temperate zone.

Factors influencing the distribution and abundance of diaptomid copepods in high-elevation lakes in the Pacific Northwest, USA - W. J. Liss; G. L. Larson; E. A. Deimling; L. M. Ganio; R. L. Hoffman; G. A. Lomnicky (Hydrobiologia, 1998)

Effects of Rock Climbing on Populations of Presettlement Eastern White Cedar ( Thuja occidentalis ) on Cliffs of the Niagara Escarpment, Canada - P. E. Kelly; D. W. Larson (Conservation Biology, 1997)
Cliffs of the Niagara Escarpment support a self‐sustaining presettlement forest of eastern white cedar ( Thuja occidentalis L.) in which some trees are over 1000 years old. Many of the cliffs are also popular locations for recreational rock climbing. Our study employed a stratified random sampling design to assess the impact of rock climbing on populations of cliff‐face and cliff‐edge trees. Tree density and age structure were compared between four climbed and three unclimbed sites in the vicinity of Milton, Ontario. Signs of physical damage were also recorded for the trees sampled at each site. The results showed that living tree density on the cliff face was lower in climbed areas. The age structures of these forests showed that the numbers of older and younger age classes have been reduced on climbed cliff faces compared with unclimbed areas. A high percentage of trees on climbed cliff faces showed evidence of damage by humans. These trends were not as apparent on cliff edges where other disturbances have affected age structure. We recommend that cliff faces be explored for the presence of presettlement forest and that recreation managers of lands with exposed cliff faces incorporate rock climbing considerations into their management plans. Monitoring programs would help track levels of disturbance. Education of the climbing community would be the most effective long‐term solution to limiting disturbance in sensitive areas.

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)

Potato research men confer in Wisconsin - R. W. Hougas; R. H. Larson (American Journal of Potato Research, 1954)